Pemanfaatan Media Pembelajaran Kreatif sebagai Wujud Profesionalisme Guru Kelas I-B SD Negeri 5 Menteng Palangka Raya - Kezia Kezia; Hermika Purmelia; Tiara Bunga; Anggie Anggie; Angela Perina Juniar; Miska Apriyana (Lembaga Pengembangan Kinerja Dosen, 2026)
The use of creative learning media is a form of effort that teachers can make to create an interesting, interactive and enjoyable learning process for students. The use of creative learning media is also a form of teacher professionalism in managing learning in accordance with technological developments and student needs. This study was conducted to determine how teachers utilize creative learning media and how the use of these media reflects the professionalism of class 1B teachers at SD Negeri 5 Menteng Palangka Raya. The method in this study used a descriptive qualitative method. Data collection techniques used included interviews, observation and documentation. Data analysis techniques in the study used the interactive model of Miles and Huberman which includes data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of the study in class 1B SD Negeri 5 Menteng Palangka Raya, showed that class 1B teachers were able to utilize various creative learning media, such as syllable wheels, Smartboards/Smart TVs, picture media, and marbles and straws in mathematics learning. The use of creative learning media can increase student interest in learning, activeness, motivation, focus, and learning outcomes. The use of creative learning media also reflects teacher professionalism in creating engaging, innovative, and student-centered learning. Research shows that the use of creative learning media has a positive impact on supporting learning success and reflects teacher professionalism.